CORPORATE LIQUIDITY MANAGEMENT AND FIRM FINANCIAL PERFORMANCE (American Journal of Business Management, Economics and Banking, 2024)
This study examines corporate liquidity management and firm financial performance. The broad objective of the study is to examine the effect of receivable period on firm financial performance of listed consumer goods companies in Nigeria and also to evaluate the effect of payable period on firm financial performance of listed consumer goods firms in Nigeria. The secondary source of data collection was adopted in the study where the purposive sampling technique was used to select a sample size of ten (10) listed consumer goods firms in Nigeria. Ordinary Least Square regression analysis was used in this study and the findings revealed that payable period has significant effect on firm financial performance of listed consumer goods firms in Nigeria and that inventory days has significant effect on firm financial performance of listed consumer goods firms in Nigeria. The study recommended among others that management of listed firms should concentrate effort on reducing the high variability of accounts receivable period and that firms should emphasize to increase sales to increase inventory turnover to achieve maintainable competitive advantage through managing inventory to optimal level so as to maximize profitability.